Does emotional intelligence impact team performance in construction projects? Exploring the mediating role of trust and moderating role of work status - Ariba Abid; Aamer Hanif; Amna Khan (Business Review, 2022)
Emotional intelligence (EI) is an essential part of the many types of intelligences an individual possesses. The outcome of interactions in personal life as well as within the organization depend upon how high or low the Emotional Quotient (EQ) is. Organizations, nowadays, specifically design tests for hiring people with higher EQ since the emotional intelligence of a team member leaves an impact on its performance. The major goal of this research is to investigate the relationship between emotional intelligence and team performance, as well as the impact of employee work status on these two. The research also examines the mediating role of trust among team members on team performance in projects. Responses from 346 participants working for construction projects have been used for analysis. The results showed that emotional intelligence is an important factor in construction projects as it affects team performance in projects while trust mediates the relationship between team emotional intelligence and team performance. Work status plays a moderating role for emotional intelligence and its outcome on project team performance. A limitation of this research is conducting analysis in construction industry only which future studies could be done in different occupational sectors considering various management positions. Additionally, interviews could be conducted for future studies with additional manpower such as daily wagers and contractual employees in the construction sector.